A study on housing condition and related service facilities for garment workers in Savar, Dhaka, Bangladesh - A. N. Kakon; A. Harisah; N. Mishima; M. Begum (Lowland Technology International, 2016)
Now-a-days the industrial revolution is taking place in Bangladesh like the other developing countries. The number of industries is increasing resulting the increased number of migrant people as workers. This large amount of people demands housing. To meet this demand, the land owners are constructing houses without considering the quality. This study tends to explore the existing housing condition of garment workers in a sub-city Savar, near Dhaka. All the information about the garments workers were collected by observation, questionnaire survey and personal interview method. The aspects that mainly considered in this study were type and material of house, size of room and occupancy, related facilities and services such as water supply, electricity, drainage, solid waste management and so on. It was found that the garment workers usually rent a single room in a group housing whatever the family size is. In a group housing a minimum of 5 and maximum 35 family lived. They shared the kitchen, toilet and bathroom. A considerable number of workers (about 40%) were still use wood in the kitchen. Corrugated Iron sheet was the main housing material as well as brick, concrete, bamboo and mud were used. The workers living in the study area faced the problems of frequent load shedding, lack of proper drainage system and absence of solid waste management system. In fact, the garment workers are rural migrants and inexperienced in urban life. They are not concerned about the facilities they should get with housing.